Exploring genetic contributors to neuroprotection from AD pathologies: A genome‐wide association study: Genetics/genetic factors of Alzheimer's disease. (7th December 2020) - Seto, Mabel; Mahoney, Emily R.; Dumitrescu, Logan; Engelman, Corinne D.; Deming, Yuetiva; Albert, Marilyn S.; Johnson, Sterling C.; Zetterberg, Henrik; Blennow, Kaj; Jefferson, Angela L.; Hohman, Timothy J.
Abstract: Background: Preclinical Alzheimer's disease (AD) is a term describing individuals who harbor neuropathological hallmarks of AD but are asymptomatic. We hypothesize that common genetic variation contributes to neuroprotection from AD pathology. More specifically, we tested whether genetic variation modifies the association between AD pathology (measured by CSF biomarkers) and neurodegeneration (measured by hippocampal volume). Method: MRI measurements of hippocampal volume and CSF measures of amyloid (Aβ42 ) and tau were obtained from 1, 073 individuals of European descent from four longitudinal aging cohort studies (age = 70.7 ± 8.7; female = 47%; normal cognition = 38%). Data were harmonized leveraging established procedures to account for differences in site, data acquisition, and processing. A genome‐wide association study was performed using mixed‐effects regression models to assess SNP x CSF biomarker interactions on hippocampal atrophy. Covariates included age, sex, population principal components, cohort, and time. Result: We identified a locus that modifies the association between baseline CSF Aβ42 and hippocampal atrophy in an intronic region of the SEMA5B gene (index SNP = rs62263260; p = 1.97e‐8; MAF = 0.12; Figure 1). Carriers of the rs62263260 minor allele showed a faster rate of hippocampal atrophy, particularly among those harboring high levels of amyloid pathology. This variant is also an eQTL for SEMA5B in brain tissue (GTEx p = 4.80e‐4), where minor allele carriers express higher levels of SEMA5B, suggesting that lower SEMA5B expression may provide neuroprotection. Additionally, we identified a locus that modifies the association between baseline CSF p‐tau and hippocampal atrophy on chromosome 3 proximal to the SATB1 gene (index SNP = rs116216974; p = 1.62e‐8, MAF = 0.02%). Carriers of the rs116216974 minor allele had a slower rate of hippocampal atrophy in the presence of high baseline p‐tau pathology compared to non‐carriers. No eQTLs were reported for rs116216974. Conclusion: We identified two independent genetic loci that modify the association between AD biomarkers and neurodegeneration. SEMA5B is implicated in synapse elimination, and increased elimination may occur in the presence of amyloid pathology. SATB1 knockdown in mice is associated with increased microglial activity, suggesting that regulating the immune response to p‐tau may be important for neuroprotection. This study also demonstrates that identifying genetic factors contributing to neuroprotection from AD pathology may help elucidate mechanisms behind asymptomatic AD.